Penerapan Metode Kangguru pada Bayi BBLR - MR, Rifka Riska; Wa Ode Sri Asnaniar; Nur Ilah Padhila; Sunarti, Sunarti (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2023)
Kangaroo Mother Care (KMC) is one of the non-pharmacological measures in handling the incidence of LBW. The success of KMC is supported by several factors, namely knowledge, attitudes and family support. This study aims to determine the factors associated with Kangaroo Mother Care (KMC) in low birth weight (LBW) infants in Sorowako Village. The research design used is a quantitative research with a cross sectional approach. This research was conducted in Sorowako Village in April 2022. The sample was determined using a total sampling technique with a sample size of 30 respondents. The relationship test was carried out using the chi-square statistical test with a significance level of < 0.05. The results showed that the majority of mothers had less knowledge as many as 17 people (56.7%), the majority of mothers had a good attitude as many as 17 people (56.7%), and the majority of mothers had good family support as many as 16 people (53.3%). ). There is a relationship between mother's knowledge and the application of the kangaroo method (ρ = 0.001), there is a relationship between mother's attitude and the application of the kangaroo method (ρ = 0.004) and there is a relationship between family support and the application of the kangaroo method (ρ = 0.002). The conclusion of this study is that there is a relationship between knowledge, mother's attitude and family support with the application of the kangaroo method. Therefore, it is hoped that mothers who give birth to LBW babies can learn about LBW and KMC and can apply them at home. It is hoped that there will be further research related to other factors that affect KMC.